Marketing Communication Success Through Fandom Activities in the Music Industry K-Pop Fandom Case Study - Susi Yunarti; Wijayanti; Dian Harmaningsih (International Journal of Marketing and Digital Creative, 2025)
As is known, the Korean wave, which has gone global along with a widespread fandom community, has developed and actively participated, playing a key role in advancing the Korean music industry in the form of K-pop. It is a social dynamic by which one community can influence an entire industry. This article aims to explain how K-pop fandom activity is a part of the marketing mix that contributes to the success of music production. The activity of the community, initially, was just for communication and information sharing, and it evolved into a marketing communication process. We collect data from both written materials exposed through news and information media, such as Kompasiana.com and Koreaboo.com, as well as scientific writings in accredited Open Journal System and Web of Science databases, with a focus on the last five years (2020-2024). Numerous articles have examined the development and success of K-pop, fandom activities, and music album sales. Meanwhile, the data collected through interviews utilizes the results of interviews with a third-party service, QuestionAI. 2021. For data analysis, we categorize and reduce the data before conducting thematic analysis. Get resource triangulation by literature study. The research results show that fandom activity serves as a form of marketing communication. In this case, K-pop fandom is not only the target of marketing but also an active promoter of album sales. Suitable to the theory of "participatory culture" by Jenkins, complete with the theory of marketing strategy as explained by Kotler and Armstrong. Fandom has played a significant role in fostering parasocial relationships between fans and K-pop idol members. Fandom activities serve as a successful marketing communication tool to promote and increase album sales.